RENTENIR (ANALISIS TERHADAP FUNGSI PINJAMAN BERBUNGA DALAM MASYARAKAT ROKAN HILIR KECAMATAN BAGAN SINEMBAH DESA BAGAN BATU ) - Ilas Korwadi Sibero (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The high level of economic needs of society and economic competition at the present time cause large demands and needs of society so that, making them will perform a variety of ways in order to obtain a better life. Different ways by society not pursued by others in a way to get capital by way of debt, of course, there are indebted to moneylenders, banks and other institutions. But in reality many people are still owed by loan sharks, especially in the villages that I researched in the Rokan Hilir Kecamatan Bagan Sinembah Bagan Batu Village. This study focused on sharks (Analysis Of Interest Bearing Debt In Rokan Hilir Society Kecamtan Sinembah Bagan Batu village. And this study discusses the work system and its interaction moneylenders and loan sharks relationships with its customers. The approach of this research uses qualitative analysis that will explain the working system moneylenders, why the public interest to borrow on moneylenders and function and dysfunction of the moneylenders. the results of this study show that people are much dependence on moneylenders due process and easy loan terms when compared with other loans as well as the efficiency of time and energy. and given the socialization of cooperative government borrowing not fully understood and known by the public so that many people are forced to borrow the loan shark with installment system that they agree between moneylenders and customers. Key Words: Money Lenders, Relationship, Analysis